(untitled) (Journal of Forensic Medicine & Toxicology, 2017)
Poisoning is a global public health problem with WHO estimates of 193, 460 deaths and 10.7 million years of healthy life (Disability Adjusted Life Years, DALYs) lost due to poisonings each year. Majority of the poisonings are in developing countries and occur in rural and agricultural communities. The objectives were to generate a database of poisoning deaths and cases and to gather information on epidemiology of common poisonings. There were 98 deaths due to poisoning in nine years period and most were suicidal in nature. Among the 397 cases of poisoning treated at the health facility in three years, most of the victims were females and in the age group of 15-60 years. The median distance covered to reach the health facility was three hours while the median time taken was 60 minutes. The time of exposure was mostly night hours and most cases were venomous bites and stings followed by organophosphorus poisoning.